2016
DOI: 10.1007/s10902-016-9770-9
|View full text |Cite
|
Sign up to set email alerts
|

Free to Be Happy: Economic Freedom and Happiness in US States

Abstract: While the measurement of subjective well-being and its usefulness as a policy objective is a matter of contention, a burgeoning field of happiness economics is emerging. This paper examines the relationship between the institutions of economic freedom and happiness as reported by respondents to the Generalized Social Survey (GSS) in the United States. GSS responses are matched via geocode to state of residence. This allows individual responses in the GSS to be matched to institutional characteristics of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Inglehart and Klingemann ( 2000 ), Veenhoven ( 2000 ), Frey and Stutzer ( 2002 ), Inglehart et al. ( 2008 ), Gehring ( 2013 ), Graafland and Compen ( 2015 ), Spruk and Kesšeljević ( 2016 ), Jackson ( 2017 ) and Nakazato et al. ( 2017 ).…”
mentioning
confidence: 99%
“…Inglehart and Klingemann ( 2000 ), Veenhoven ( 2000 ), Frey and Stutzer ( 2002 ), Inglehart et al. ( 2008 ), Gehring ( 2013 ), Graafland and Compen ( 2015 ), Spruk and Kesšeljević ( 2016 ), Jackson ( 2017 ) and Nakazato et al. ( 2017 ).…”
mentioning
confidence: 99%
“…The previous pieces of literature noticed some positive and some negative association between freedom and happiness. Jackson [16] has found the positive association between economic freedoms with the individuals reported happiness and state average level of happiness in the USA. Ariel R Belasen and Hafer [17] found no relationship between economic freedom and well-being.…”
Section: Empirical Foundation and Construction Of Research Hypothesismentioning
confidence: 99%
“…Several studies have conducted in the United States about the relationship between economic freedom and happiness. Jackson [16] examined the relationship between the institutions of economic freedom and happiness and found that the level of economic freedom in the United States has a positive association with both individuals reported happiness and state average level of happiness. Ariel R Belasen and Hafer [17] used the cross-sectional econometric model and found that there is no relationship between economic freedom and well-being but overtimes if the economic freedom is changed then they found a positive association and statistically significant result between economic freedom and happiness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, sufficient research has been done on subjective well-being and the personality construct of emotional intelligence alone to enable a meta-analysis of the relationship (Sanchez-Alvarez et al 2016). Moreover, the effect on state happiness of luck as an external and chance event, such as a lottery win or debilitating accident, has, additionally, long been a subject of scholarly interest (Brickman et al 1978;Diener et al 2006;Lucas 2007;Luhmann and Eid 2009;Jackson 2017). However, the systematic and direct investigation of any association between trait happiness and trait luck beliefs has hitherto been absent.…”
Section: Introductionmentioning
confidence: 99%